Spinal Anesthesia with a Low Dose of Hyperbaric Bupivacaine plus Fentanyl versus Hyperbaric Bupivacaine for Transurethral Resection of Prostate surgery: Hemodynamic Effects, Duration of Analgesia and Motor Block - Mahnaz Shahverdi; Amir Sabertanha; Fahimeh Nikraftar; Gholamhossein Mahmoudirad (Mashhad University of Medical Sciences, 2020)
Background: Spinal anesthesia is the most prevalent anesthetic method used for transurethral resection of the prostate (TURP) surgery. Lower motor block and fewer side effects can be achieved by lower doses of anesthesia. Aim: The present study aimed to compare the effects of Spinal anesthesia with a low dose of hyperbaric bupivacaine plus fentanyl with hyperbaric bupivacaine for TURP surgery on hemodynamic effects, duration of analgesia, and Motor block. Method: This randomized-controlled study was conducted on 62 patients undergoing TURP surgery within 2017-18. BF group received 0.5% hyperbaric bupivacaine(1mg) 0.2 ml+fentanyl (20µg) 0.4 ml+5% dextrose 1.4ml, while B group received 0.5% hyperbaric bupivacaine (10mg)2ml. Bromage scale and Visual Analog Scale of pain and Nausea were used. The obtained data were analyzed in SPSS software version (20). Results: Groups were homogenous in terms of demographic characteristics. The time to reach the sensory level of T10 was significantly longer in the BF group, compared to the B group (P<0.001). The motor block score was less in the BF group than the B group. The mean total recovery time of the sensory block to L5 in the BF group was significantly lower than that of the BF group (P<0.001). The mean score of nausea severity during surgery was significantly lower in the BF group, compared to the B group (P=0.02). The hemodynamic stability was higher in the BF group. Implications for Practice: A combination of 1mg bupivacaine with 20μg fentanyl could be used for anesthesia in TURP surgery as an effective method to provide sufficient analgesic effects, as well as lower motor block and side effects.